Two-year weight, risk and health factor outcomes of a weight-reduction intervention programme: Primary prevention for overweight in a multicentre primary healthcare setting - Marie Bräutigam-Ewe; Marie Lydell; Håkan Bergh; Cathrine Hildingh; Amir Baigi; Jörgen Månsson (Taylor & Francis Group, 2020)
Objective: To study the long-term effects of weight reduction, quality of life and sense of coherence in a primary health care (PHC)-based programme with two different intensities. Design: Prospective two-armed randomised intervention. Setting: Three PHC centres in south west of Sweden. Subjects: In total, 289 women and men aged 40-65 years with a BMI of 28-35 were recruited for a two-year weight-reduction programme. Participants were randomized to high-intensity or low-intensity groups. Blood samples, physical measurements and questionnaires were analysed. Participants received cookbooks and dietary lectures. The high-intensity group also received Motivational interviewing (MI), dietary advice on prescription (DAP- advice), a grocery store lecture, a website and weekly e-mails. Main outcome measures: Weight, quality of life, risks and health factors. Results: In total, 182 (64%) participants completed the 2-year follow-up. The total sample reduced their weight by 1 kg (p = 0.006). No significant differences regarding weight were found between the groups. Anxiety/depression decreased in EQ5-D (p = 0.021), EQ5-D VAS (p = 0.002) and SOC (p = 0.042). Between the groups, there were significant differences in EQ5-D usual activities (p = 0.004), anxiety/depression (p = 0.013), pain/discomfort (p = 0.041), fruit and vegetables (p = 0.005), HLV anxiety (p = 0.005), and visits to nurses (p = 0.012). Conclusion: The total population lost weight, and the high-intensity and low-intensity programmes did not result in significant differences in terms of weight. The high-intensity programme reported health benefits linked to lower levels of anxiety and depression, increased activity and intake of greens and reduced visits to physicians and nurses.Key points Both groups had a consisting weight- reduction after two years. High intensity did not lead to a significant difference in weight reduction between the groups. The high-intensity group reported more health effects, such as better quality of life, reduced anxiety, and increased greenery intake. It is unknown how much support patients in a weight- reduction programme in PHC require to succeed with weight loss and a healthy lifestyle